Serum oxidative–anti‐oxidative stress balance is dysregulated in patients with hepatitis C virus‐related hepatocellular carcinoma. Issue 10 (30th January 2013) - Nishimura, Mamoru; Takaki, Akinobu; Tamaki, Naofumi; Maruyama, Takayuki; Onishi, Hideki; Kobayashi, Sayo; Nouso, Kazuhiro; Yasunaka, Tetsuya; Koike, Kazuko; Hagihara, Hiroaki; Kuwaki, Kenji; Nakamura, Shinichiro; et al.
<x xml:space="preserve">Abstract</x> Aim Oxidative stress is associated with progression of chronic liver disease (CLD). This association is best established in chronic hepatitis C. However, the anti‐oxidative state is not well characterized. The objective of the present study was to investigate the balance of oxidative and anti‐oxidative stress in CLD patients. Methods We recruited a study population of 208 patients, including healthy volunteers (HV; n = 15), patients with hepatitis B virus (HBV)‐related CLD without or with hepatocellular carcinoma (HBV‐non‐HCC, n = 25, and HBV‐HCC, n = 50, respectively), and patients with hepatitis C virus (HCV)‐related CLD without or with HCC (HCV‐non‐HCC, n = 49, and HCV‐HCC, n = 69, respectively). Serum levels of reactive oxygen metabolites (ROM) and anti‐oxidative markers (OXY‐adsorbent test; OXY) were determined, and the balance of these values was used as the oxidative index. Correlations among ROM, OXY, oxidative index and clinical characteristics were investigated. Results Patients with CLD exhibited elevated ROM and oxidative index compared to HV. Among patients with CLD, HCV positive status correlated with increased ROM. In CLD, HCV‐HCC patients exhibited the highest ROM levels. Among HCV‐related CLD patients, lower OXY correlated with HCC positive status, but was recovered by eradication of HCC. In HCV‐HCC, lower OXY correlated with high PT‐INR. Conclusion HCV positive CLD patients displayed higher oxidative stress and HCV‐HCC patients displayed lower anti‐oxidative state. Anti‐oxidative state depression was associated with liver reservoir‐related data in HCV‐HCC and could be reversed with HCC eradication.